Annual Report - Feinstein International Center (Tufts Archival Research Center, 2005)
Strategic planning undertaken in 2004/5 has paid off. The Center has revised its research portfolio to focus on three critical themes of research: Lives and Livelihoods, Rights and Protection, and Politics and Policy. In July 2006, the Center staff moved into a new, larger space in an office building at the Tufts Medford campus, and we have opened a permanent second office in Addis Ababa. Our team of researchers, both in Medford and in Addis, has expanded over the year, and we are set to continue this expansion into 2006/7.